Identificación y Control Postcosecha de las Enfermedades del Tomate en la Florida - Michael J. Mahovic; Steven A. Sargent; Jerry A. Bartz; Elena E. Lon Kan (EDIS)
New to EDIS! HS-1080, an 11-page illustrated bulletin by Michael J. Mahovic, Steven A. Sargent, Jerry A. Bartz, and Elena E. Lon Kan, is the Spanish language version of "HS866/HS131: Identifying and Controlling Postharvest Tomato Diseases in Florida." This bulletin is designed to supplement field scouting and identification guides by describing postharvest decay pathogens important to Florida tomato packers and shippers and presenting sanitation guidelines for controlling decay pathogens during harvest and handling operations. Includes references. Originally published by the UF Department of Horticultural Sciences, March 2002, revised December 2006.